2018
DOI: 10.20344/amp.10620
|View full text |Cite
|
Sign up to set email alerts
|

CoFI - Consenso Sobre Fórmulas Infantis: A Opinião de Peritos Portugueses sobre a Sua Composição e Indicações

Abstract: Introduction: Breastfeeding has unique health benefits. Exclusive breastfeeding is recommended during the first six months of life and should be maintained during complementary feeding. Alternatively, infant formulas, which are designed to mimic human breastmilk to promote similar metabolic and growth profiles, can be used. This study aimed to assess the opinion of Portuguese paediatricians with expertise in nutrition on the composition, benefits and indications of commercialised infant formulas.Material and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
4
0
4
Order By: Relevance
“…Whey protein fractions are richer in essential amino acids compared to caseins and, therefore, the general amino acid profile found in cow milk differs from breast milk [70], corroborating the results reported herein. Babies fed IFs exhibit greater differences in plasma amino acids compared to breastfed infants, with tryptophan levels, in particular, lower in the former [25].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Whey protein fractions are richer in essential amino acids compared to caseins and, therefore, the general amino acid profile found in cow milk differs from breast milk [70], corroborating the results reported herein. Babies fed IFs exhibit greater differences in plasma amino acids compared to breastfed infants, with tryptophan levels, in particular, lower in the former [25].…”
Section: Discussionmentioning
confidence: 96%
“…Human and cow milk differ not only in the amount of proteins, but also their quality. Human milk protein contents range from 0.8 to 1.3 g•100 mL −1 , varying throughout the lactation stage, while whole cow milk contains about 3.33 g•100 mL −1 , about three-fold higher than human milk [24][25][26]. The current Brazilian legislation, which agrees with European Commission Directive 2006/141/EC recommendations, establishes a minimum protein content for phase 1 cow milk-derivative formulas of 1.8 g•100 kcal −1 and a maximum of 3.0 g•100 kcal −1 , while protein concentrations in phase 2 formulas should range between 1.8 g•100 kcal −1 to 3.5 g•100 kcal −1 [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…A study based on the Delphi method with Portuguese pediatricians specialized in infant nutrition identified that there was no consensus on the nutritional benefits of using YCF in the 2 nd year of life, although the panel agrees that these formulas have some advantages over integral cow's milk. 91 Another study concluded that GUM consumption reduced the risk of iron and vitamin D inadequacies, two nutrients often absent in the diets of young children who consume only enriched cow's milk. 76 Concisely, it seems acceptable to understand that the composition of an YCF potentially contributes to (1) decreasing the overall protein intake, which tends to be higher than the reference values for this age, (2) increase the content of essential fatty acids with the addition of long-chain polyunsaturated fatty acids (docosahexaenoic and arachidonic acids) and (3) ensure the supply of some minerals (such as iron, calcium and phosphorus), vitamins (D, B2 and B12) and fibers/prebiotics.…”
Section: Discussion On Literature Data and The Brazilian Realitymentioning
confidence: 99%
“…Estima-se que entre 2014 e 2019 tenha ocorrido um aumento de 6,8% no consumo de substitutos do leite materno, associado ao crescimento do poder de compra da sociedade. [3][4][5] Dados acerca do faturamento da indústria do leite artificial no mundo apontaram que no ano 2014 foram gastos 44,8 bilhões de dólares em vendas. Devido a isso, existe um forte trabalho dessas empresas com propagandas que projetam na sociedade a dependência de seu produto e, assim, as famílias acabam, muitas vezes, assumindo como melhor e necessário o substituto do leite materno para o crescimento e desenvolvimento do seu filho.…”
Section: Introductionunclassified